The Quranic Concept of Preventing Stigma Against Persons with Disabilities According to Imam Nawawi Al-Bantani in Tafsir Al-Munir - Muhammad Habib Ihsanudin; Siti Badi'ah; Budimansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Disability refers to physical, mental, or intellectual limitations that can affect a person's ability to perform daily activities. Stigma against people with disabilities is still a serious social problem in various parts of the world, including in Indonesia. In fact, the Qur'an has provided comprehensive guidance on how we should treat our fellow humans, including those with physical or mental limitations. This research aims to delve deeper into the concepts of the Qur'an related to the prevention of stigma against people with disabilities and how the Qur'an cracks down on stigma perpetrators, especially through the tafsir of Imam Nawawi al-Bantani in Tafsir al-Munir.This study uses a qualitative method with a literature study approach. Primary data was obtained from Tafsir al-Munir, while secondary data was obtained from various literature related to disability, the Qur'an, and tafsir. Data analysis uses a thematic method carried out by tracing relevant verses of the Qur'an, then interpreting them based on the interpretation of Imam Nawawi al-Bantani. In the Qur'an, there are letters that discuss people with physical disabilities in Surah Abassa 1-10, Surah An-Nur 61, Surah Al-Imran 49, Surah Al Fath 17 and Surah al-Maidah verse 110. In this study, the author came to the conclusion, namely: first, as fellow human beings, it is forbidden to discriminate, second, it is forbidden to be prejudiced, third, it is necessary to maintain the dignity of others, fourth, it thinks that our fellow human beings are equal, fifth, it has empathy for others, sixth, it is fair, and seventh, it is to give appreciation to people with disabilities. In general, the results of the study show that the Qur'an expressly rejects all forms of discrimination and views all human beings as equal beings before Allah SWT.